The Attractive Urban Focal Points (Journal of Planner and Development, 2019)
This paper studies attractive urban focal points, which is considered one of the most important elements of urban formation in the city and the main engine in its transformations. It regulates people’s relationship with space and contributes to human communication among the members of the society. The public space is capable of providing a range of economic, social and environmental benefits, And can be seen as vital tools and attractions to attract the largest number of users, and to emphasize the symbolism and identity of urban centers to enhance the sense of belonging by embodying the identity of the city within the elements of the urban focus. From here, the main focus of the general research was to present a specialized study on the urban focal points in the city, its types, characteristics and concepts corresponding to them, and reviewed the proposals and studies that dealt with the subject according to their research directions hence the problem of research : (There is a Lack of clarity of the attractive spatial quality behind the formation of the urban plots depending on it’s nature of the function and physical features). The research was based on its objective and the treatment of its research problem based on a main hypothesis: (The attractive value of urban centers depends on the structure of their formal structure and the nature of their urban components and their functional attractiveness).